ANDIL AGAMA DAN POLITIK KEKUASAAN DALAM KONFLIK-KONFLIK SOSIAL DAN KERUSUHAN-KERUSUHAN MASSAL DI INDONESIA - Mardimin, J. (Universitas Kristen Satya Wacana, 2018)
This paper discusses the contribution of religion and political power in social conflicts and mass riots that have occurred in Indonesia over the past three decades. This article was built based on data from field research conducted by the author in Pekalogan City and in Surakarta City after the May 1998 riots; and the results of a literature study on the struggle of people of Chinese descent in Indonesia. Based on the results of these studies it can be noted that religion and political power have a very large contributions of the occurrence of social conflicts and mass riots in Indonesia.